In the Shadow of the Wall: An Entrance into the Lives of Displaced Palestinians - Abuhasan, Ala (University of Waterloo, 2018)
What totalitarian regimes do is to—and this is what makes them extremely devastating—is they look at you and say, “You are not.” Or, “You are something else.” Or, “This event didn’t exist.” This power, that is only God’s power. If a regime, or some people, think they are God, they can have the right to make you animals or human. They can create you or kill you. And this is unbearable. So the only thing you can do—and the most subversive thing you can do—is to tell the truth. This is devastating because each time you come back with the truth, you deny their prerogative of creating a fictitious world where they can say whatever they want. Ladan Boroumand I am an estranged Palestinian born to estranged Palestinian parents. The Hagana troops, and later the Israeli forces, evacuated my grandparents from Palestine. I know Palestine in fragmented pieces, events, and experiences. I know Palestine through songs and through old family photographs. I know Palestine as a worn image vaguely existing in a photo album. I am an estranged Palestinian born to estranged Palestinian parents. When the Israeli state was born, my grandparents became refugees. Exiles. In this book, I present the Palestine I know. I introduce my homeland through snapshots of Palestinian lives. From the narrow alleys of refugee camps to the disconnected territories in the West Bank, I move through Palestine. I document it. The land, the people, the memories still exist. They continue to exist. This book is an entrance into the lives of Palestinians. It is a stand in the face of injustice—a voice against the Israeli occupation. In the words of the Palestinian poet Mahmoud Darwish, in this thesis “I don’t decide to represent anything except myself. But that self is full of collective memory.” The Palestinian lives in a constant state of exile; a state of exile that is inherited, one generation after another. This book goes through five movements. The first movement: a visit to the land through which I encounter Palestine for the first time. The second: the wound—a force cutting through the land and the continuity of Palestinian lives. The third: loss. The fourth: love. Then, a departure. Through the refrains of poetry and stories, this book reconstructs Palestine. The Palestine that continues to exist.
Keywords: Palestine; Refugee; Refugee Camps; West Bank; Photography